Mechanical properties, drying shrinkage and structural performance of coconut shell lightweight concrete. (January 2022) - Aziz, Waqas; Aslam, Muhammad; Ejaz, Muhammad Fahad; Jahanzaib Ali, M.; Ahmad, Riaz; Wajeeh-ul-Hassan Raza, M.; Khan, Azam
Highlights: Mix CBA-50 showed 9% reduction in compressive strength compare to NWC. 28-day flexural to compressive ratio for all mixes ranges b/w 11–13.5%. CBA-50 showed about 18% reduction in drying shrinkage compared to C-100. CBA-50 can be utilized in real-life structures based on its properties. RC beam made of CS + BA showed higher shear performance then other mixes. Abstract: The main concerns of civil engineering officials and researchers is to produce the structural lightweight concrete, which is cost effective, sustainable, durable and can behave satisfactorily under structural applications. Therefore, the use of industrial waste as an alternative lightweight aggregate (LWA) to build eco-friendly stable structures that have many realistic and financial benefits. Coconut shell (CS) is a waste industrial by-product and was successfully utilized to produce reasonable strength lightweight aggregate concrete. Four different types of concrete mix were developed with first three samples having 0%, 50%, 100% replacement of NWA with coarse CS, however, in fourth mixture, the combination of NWA and CS aggregates was considered at 50% substitution levels and in addition, the 25% of cement was replaced with bagasse ash. In conclusion, it was found that the combinations of CS and NWA increases the workability of the concrete mixes and showed 28-day compressive strength between 30 and 39 MPa with oven-dried density range of 1856 to 2103 kg/m 3 . Mix containing 50% CS and 25% bagasse ash showed significantly better performance in terms of drying shrinkage with the percentage reduction of about 18% compared to the coconut shell concrete (CSC), and this value was about 14% higher than the conventional normal weight concrete (NWC). In shear behavior, the contribution of CS and NWAs with 25% of cement replacement with bagasse ash showed higher shear performance compared to other beams containing 50% and 100% Coconut shell aggregates (CSA).